Rancang Bangun Sistem Informasi Kelompok Wanita Tani (Kwt) Kota Prabumulih Barat Berbasis Web Menggunakan Metode V - Samelia, Regita; Nur Aini Hutagalung; Suhartini (Elkom: Jurnal Elektronika dan Komputer, 2023)
In the current era of globalization, the use of computer technology has been widely used, including in the operations of non-formal organizations such as farmer women's groups (KWT), one of which is in administration, activities, schedules, sales. agenda, and reporting is still manual, namely with bookkeeping records and does not yet have a system for this. Given these problems, the right solution is to create a web-based information system for women farmer groups (kwt). In analyzing and designing, the author uses a software development method that uses the V-Model method, which is an extension of the waterfall model. It is called expansion because the stages are similar to those in the waterfall model. If in the waterfall model the process is carried out linearly, then in the V model the process is branched. In this V model, the relationship between the software development stage and the testing phase is described. The purpose of this research is to produce an information system that can make it easier for the kwt to do administration. activity. timetable. sale. agenda. and reporting without recording with the books.